Kualitas Pelayanan Terhadap Loyalitas Nasabah melalui Kepuasan Nasabah BNI - NURFATWA ANDRIANI YASIN; Afriyani; Kurniawaty (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2022)
This study aims to determine the relationship between service quality from customer meetings to customer loyalty through customer satisfaction and the relationship between service quality and customer loyalty through customer satisfaction BNI Makassar Regional Office. It is hoped that this research can help BNI to identify and understand the effect of service quality on BNI customer satisfaction and loyalty. The data analysis method used is path analysis. The object of research is the customers of BNI Makassar Regional The object of research is the customers of BNI Makassar Regional Office totaling 100 people with the sampling method using direct census techniques for 3 weeks the researchers are at BNI Makassar Regional Office. The results of the study indicate that there is a positive relationship between the quality of customer meeting service and customer loyalty through customer satisfaction, and there is a positive relationship between service quality and customer loyalty through customer satisfaction. The results of this study found that maintaining customer loyalty is not an easy thing, therefore BNI is expected to be able to improve its services and provide guarantees for all financial transactions carried out, reducing the risks caused by Human Errors by increasing the professional attitude of BNI staff and employees to minimize staff and employees and always ready to provide excellent service without compromising other aspects.